KMT-2021-BLG-1547Lb: Giant microlensing planet detected through a signal deformed due to source binarity - Han C; Zang W; Jung YK; Bond IA; Chung S-J; Albrow MD; Gould A; Hwang K-H; Ryu Y-H; Shin I-G; Shvartzvald Y; Yang H; et al. (EDP Sciences, France, 2023)
Aims. We investigate the previous microlensing data collected by the KMTNet survey in search of anomalous events for which no precise interpretations of the anomalies had been suggested. From this investigation, we find that the anomaly in the lensing light curve of the event KMT-2021-BLG-1547 is approximately described by a binary-lens (2L1S) model with a lens possessing a giant planet, but the model leaves unexplained residuals. Methods. We investigated the origin of the residuals by testing more sophisticated models that include either an extra lens component (3L1S model) or an extra source star (2L2S model) on top of the 2L1S configuration of the lens system. From these analyses, we find that the residuals from the 2L1S model originate from the existence of a faint companion to the source. The 2L2S solution substantially reduces the residuals and improves the model fit by δ x 2 = 67.1 with respect to the 2L1S solution. The 3L1S solution also improves the fit, but its fit is worse than that of the 2L2S solution by δ x 2 = 24.7. Results. According to the 2L2S solution, the lens of the event is a planetary system with planet and host masses (Mp/MJ, Mh/M·) = (1.47-0.77+0.64, 0.72-0.38+0.32) lying at a distance DL = 5.07-1.50+0.98 kpc, and the source is a binary composed of a subgiant primary of a late G or an early K spectral type and a main-sequence companion of a K spectral type. The event demonstrates the need for sophisticated modeling of unexplained anomalies if one wants to construct a complete microlensing planet sample.
Keywords: gravitational lensing; micro / planets and satellites; detection